Sagot :
The answer is y = (x + 1)^2.
Step-by-step explanation:
The vertex form for a quadratic function is y = a(x - h)^2+ k. Furthermore, the vertex form of a quadratic function can be represented as a coordinate (h, k). Wherein, (h, k) is the same as with (x, y).
Note:
- f(x) can also be written as y
- h = horizontal change/ shift
- k = vertical change/ shift
Solution:
Always follow this pattern, y = a(x - h)^2 + k.
y = x^2 + 2x + 1
y = (x^2 + 2x) + 1
- Make (x^2 + 2x) into a perfect square trinomial form.
y = (x^2 + 2x + 1) + 1 - 1
- Make (x^2 + 2x + 1) into a square of binomial form, then combine the outside terms.
y = (x + 1)^2
- Therefore, I can conclude that the coordinate of this vertex is (-1,0).
- Hope it helps.
#CarryOnLearning